2014
DOI: 10.1353/csd.2014.0064
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Relationships Between Perceived Support From Close Others, Goal Commitment, and Persistence Decisions at the College Level

Abstract: Right click to open a feedback form in a new tab to let us know how this document benefits you.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 57 publications
0
24
0
1
Order By: Relevance
“…The literature on predicting graduation, persistence from one year to the next, as well as intention to graduate from colleges and universities has been heavily influenced by the work of Bean (1982) and Tinto (1975). A large number of studies have examined pre-entry characteristics, such as parental education, age, gender, financial need, high school performance, school and student demographics such as full vs. part-time studies, academic and social integration, student contact with faculty, student engagement, as well as personality, psychosocial adjustment, and social support (Chen, 2012;Hudy, 2007;Jorgensen, Ferraro, Fichten, & Havel, 2009;Heller & Cassady, 2015;Luke, Redekop & Burgin, 2015;National Center for Education Statistics, 2010;Strom & Savage, 2014). Yet, in spite of strong interest and a vast literature, prediction of graduation, drop-out, and intention to graduate have a relatively poor track record, even when a large number of variables such as grades, gender, and survey results are included (e.g., Heller & Cassady, 2015;Jorgensen et al, 2009;Jorgensen, Fichten, & Havel, 2008;Luke, Redekop & Burgin, 2015).…”
Section: Why the Topic Is Importantmentioning
confidence: 99%
“…The literature on predicting graduation, persistence from one year to the next, as well as intention to graduate from colleges and universities has been heavily influenced by the work of Bean (1982) and Tinto (1975). A large number of studies have examined pre-entry characteristics, such as parental education, age, gender, financial need, high school performance, school and student demographics such as full vs. part-time studies, academic and social integration, student contact with faculty, student engagement, as well as personality, psychosocial adjustment, and social support (Chen, 2012;Hudy, 2007;Jorgensen, Ferraro, Fichten, & Havel, 2009;Heller & Cassady, 2015;Luke, Redekop & Burgin, 2015;National Center for Education Statistics, 2010;Strom & Savage, 2014). Yet, in spite of strong interest and a vast literature, prediction of graduation, drop-out, and intention to graduate have a relatively poor track record, even when a large number of variables such as grades, gender, and survey results are included (e.g., Heller & Cassady, 2015;Jorgensen et al, 2009;Jorgensen, Fichten, & Havel, 2008;Luke, Redekop & Burgin, 2015).…”
Section: Why the Topic Is Importantmentioning
confidence: 99%
“…Bean and Metzner (1985) argued that a key factor in nontraditional student attrition was family responsibilities. Furthermore, other literature has demonstrated that family support is key to academic success (Christenson, Rounds, & Gourney, 1992;Dennis, Phinney, & Chuateco, 2005;Palmer, Davis & Maramba, 2011;Strom & Savage, 2014). More specifically, Berkove (1979) found that husband support was important for student success, but interestingly, the women in their study reported little change in their domestic role, which increased stress levels.…”
Section: Work-family-school Satisfactionmentioning
confidence: 83%
“…Madonna and Philpot (2013) found an attractive goal that is believed to be obtainable is more likely to bring the motivation needed to act on it. Strom and Savage (2014) found that a commitment to graduating did indeed impact an intention to persist. Dennis, Phinney, & Chuateco, (2005) found that motivational factors in attending college, such as intellectual curiosity and desiring the ability to have a rewarding career, are key factors in college adjustment and commitment, even after controlling other features such as gender, ethnicity, economic status and high school GPA.…”
Section: Against the Odds: Perceptions Impacting Continuationmentioning
confidence: 94%
“…The findings of this study were in alignment with the literature, indicating the community college transfer pathway requires a support system for successful navigation. Strom and Savage's (2014) research found that peers and family not only influence the initial decisions about college, such as where to attend and having a goal to graduate, but that family support in particular has a subsequent impact on students as to remaining committed to the goal of graduating with a college degree. Cheng, Ickes, and Verhofstadt (2012) found that perceived family social support had a positive impact on grade point average.…”
Section: It Takes a Village: Supportive Resourcesmentioning
confidence: 99%